Congenital Heart Diseases Detected by Prenatal Fetal Echocardiography and Associated Extracardiac Anomalies - Hayrullah Alp; Mesut Küçükosmanoğlu; Barış Sever; Ceyhan Baran; Mehmet Sevgili; Ahmet Midhat Elmacı; Esma Keleş Alp (Journal of Pediatric Research, 2019)

(untitled)
Aim:The aim of this study is to determine the relationship between extracardiac abnormalities and congenital heart diseases in fetuses that were referred for fetal echocardiography due to a variety of reasons.Materials and Methods:A total of 1,158 pregnant woman whose fetal echocardiograms and detailed fetal anomaly scanning were performed between June 2017 and July 2018 were included in this study. The documents of the pregnant women were reviewed retrospectively. Those fetuses who were determined to have various organ anomalies and congenital heart defects were recorded.Results:While 664 pregnant women were in the low-risk group, 494 pregnant women were in the high-risk group in the study. Congenital heart defects were detected in a total of 38 pregnant women (3.28%). The prevalence of all gastrointestinal system, urinary system and central nervous system anomalies were 5.35%, 3.79% and 6.73%, respectively. Interventricular septum, aorta, pulmonary and tricuspid valves associated with congenital heart diseases were found to be mostly related with these organ anomalies.Conclusion:Gastrointestinal system and central nervous system anomalies were found to be mostly associated with congenital heart diseases. Also, the interventricular septum, aortic, pulmonary and tricuspid valves’ anomalies were the most frequently detected congenital heart diseases in these situations.